Business ecosystems policy in Stra.Tech.Man terms: The case of the Eastern Macedonia and Thrace region - Charis Vlados; Dimos Chatzinikolaou (Journal of Entrepreneurship, Management and Innovation)
In the current state of globalization’s restructuring, numerous studies are examining policies to strengthen local entrepreneurship and productive systems, in terms of clusters and ecosystems. In this article, we apply and extend the Stra.Tech.Man approach to entrepreneurial dynamics as an alternative base of articulating a business ecosystems development policy. By studying the case of the Eastern Macedonia and Thrace region, one of the less developed regions in Greece, we find that there are possibilities for using the Stra.Tech.Man approach to imprint, record and, by extension, give the possibility of strengthening the strategic, technological, and managerial capacity of the “cells” of specific business ecosystems. In this context, the aim of this study is to outline a new possible direction for policy planning and implementation, in order to expand the local business ecosystems’ innovative and competitive competence, especially in the context of a less developed region, by the usage of the ILDI (Institutes of Local Development and Innovation) mechanism. In this direction, we present an “introductory” and qualitative field research we carried out in the region of Eastern Macedonia and Thrace, on a sample of SMEs, in diagnostic terms of Stra.Tech.Man physiology